Artificial intelligence and its role in the labor market and financial sector itself: US point of view - Havryk, Alina; Nazarova, Tetiana (International Science Group, 2024)
The article examines the role and impact of artificial intelligence (AI) in the financial sector to determine its impact on the future workforce and the US's pivotal role in shaping technology trends around the world. Drawing from labor economics and sociology, it analyzes how AI adoption affects job roles, skills demanded, and employment patterns in the financial industry. The work analyzes the current state of the use of AI in finance, examines its impact on changes in labor markets and employment structure, and identifies key factors shaping the development of the financial sector under the influence of technological innovation.
Keywords: Artificial Intelligence; innovation; labor market effects